Six new species of the subgenus Homoneura (Diptera: Lauxaniidae: Homoneura) from Yintiaoling Nature Reserve, Chongqing, China - You, Pengyan; Chen, Xulong; Li, Wenliang (Zootaxa, 2025)
The subgenus Homoneura (Homoneura) is nearly cosmopolitan, with more than 700 described species distributed in all zoogeographical regions, except the Neotropical region. Here, we describe six new species of the subgenus from Yintiaoling Nature Reserve, Chongqing, China: Homoneura (Homoneura) mediclavata sp. nov. in the H. (H.) abnormis group; H. (H.) claviformis sp. nov. in the H. (H.) laticosta group; H. (H.) nigrapicalis sp. nov. and H. (H.) longicerca sp. nov. in the H. (H.) notostigma group; H. (H.) caperata sp. nov. and H. (H.) fuscifemoris sp. nov. not placed in any species group. Detailed descriptions and diagnosis of each species are provided.